ChemInform Abstract: Synthesis, Structure and Electrical Properties of a New Tin Vanadium Selenide. Issue 31 (11th July 2013) - Atkins, Ryan; Disch, Sabrina; Jones, Zachary; Haeusler, Ines; Grosse, Corinna; Fischer, Saskia F.; Neumann, Wolfgang; Zschack, Paul; Johnson, David C.
Abstract The intergrowth compound (SnSe)1.15VSe2 is prepared from the elements by physical vapor deposition using the modulated elemental reactant technique.